Reasons for PrEP Discontinuation After Navigation at Sexual Health Clinics: Interactions Among Systemic Barriers, Behavioral Relevance, and Medication Concerns. (1st July 2022) - Unger, Zoe D.; Golub, Sarit A.; Borges, Christine; Edelstein, Zoe R.; Hedberg, Trevor; Myers, Julie
Abstract : Background: Pre-exposure prophylaxis (PrEP) for HIV prevention requires engagement throughout the PrEP care continuum. Using data from a PrEP navigation program, we examine reasons for PrEP discontinuation. Setting: Participants were recruited from New York City Health Department Sexual Health Clinics with PrEP navigation programs. Methods: Participants completed a survey and up to 3 interviews about PrEP navigation and use. This analysis includes 94 PrEP initiators that were PrEP-naive before their clinic visit, started PrEP during the study, and completed at least 2 interviews. Interview transcripts were reviewed to assess reasons for PrEP discontinuation. Results: Approximately half of PrEP initiators discontinued PrEP during the study period (n = 44; 47%). Most participants (71%) noted systemic issues (insurance or financial problems, clinic or pharmacy logistics, and scheduling barriers) as reasons for discontinuation. One-third cited medication concerns (side effects, potential long-term side effects, and medication beliefs; 32%) and behavioral factors (low relevance of PrEP because of sexual behavior change; 34%) as contributing reasons. Over half (53.5%) highlighted systemic issues alone, while an additional 19% attributed discontinuation to systemic issues in combination with other factors. Of those who discontinued, approximately one-third (30%) restarted PrEP during the follow-up period, citing resolution of systemic issues or behavior change that increased PrEP relevance. Conclusions: PrEP continuation is dependent on interacting factors and often presents complex hurdles for patients to navigate. To promote sustained engagement in PrEP care, financial, clinic, and pharmacy barriers must be addressed and counseling and navigation should acknowledge factors beyond sexual risk that influence PrEP use.